Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/adhm.202300823
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Confinement Modulates Macrophage Response in Microporous Annealed Particle (MAP) Scaffolds

Abstract: Macrophages are essential in the initiation, maintenance, and transition of inflammatory processes such as foreign body response and wound healing. Mounting evidence suggests that physical factors also modulate macrophage activation. 2D in vitro systems demonstrate that constraining macrophages to small areas or channels modulates their phenotypes and changes their responses to known inflammatory agents such as lipopolysaccharide. However, how dimensionality and pore size affect macrophage phenotype is less ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Microfluidic devices and microgels were made as previously described. [ 34 ] Briefly, 8 arm PEG‐VS microgels were formulated at a final concentration of 5 wt% w/v PEG‐VS (JenKem technology) in 0.3 m triethanolamine (Sigma) with 500 µ m RGD (Ac‐RGDSPGERCG‐NH2, GenScript), 500 µ m K‐peptide (Ac‐FKGGERCG‐NH2, GenScript), and 500 µ m Q‐peptide (Ac‐NQEQVSPLGGERCG‐NH2, GenScript) and crosslinked at a 0.6 VS to thiol ratio with di‐thiol matrix metalloproteinase sensitive peptide (Ac‐GCRDGPQGIWGQDRCG‐NH2, GenScript) plus 10 µ m AlexaFluor‐647 (ThermoFisher). For 40 and 70 µm microgel generation, a four‐inlet microfluidic device was used.…”
Section: Methodsmentioning
confidence: 99%
“…Microfluidic devices and microgels were made as previously described. [ 34 ] Briefly, 8 arm PEG‐VS microgels were formulated at a final concentration of 5 wt% w/v PEG‐VS (JenKem technology) in 0.3 m triethanolamine (Sigma) with 500 µ m RGD (Ac‐RGDSPGERCG‐NH2, GenScript), 500 µ m K‐peptide (Ac‐FKGGERCG‐NH2, GenScript), and 500 µ m Q‐peptide (Ac‐NQEQVSPLGGERCG‐NH2, GenScript) and crosslinked at a 0.6 VS to thiol ratio with di‐thiol matrix metalloproteinase sensitive peptide (Ac‐GCRDGPQGIWGQDRCG‐NH2, GenScript) plus 10 µ m AlexaFluor‐647 (ThermoFisher). For 40 and 70 µm microgel generation, a four‐inlet microfluidic device was used.…”
Section: Methodsmentioning
confidence: 99%
“…[78,79] Previous research has shown that GHS comprising varying microgel sizes influence cell infiltration and macrophage polarization. [80,81] GHS made up of ≈48 or ≈146 μm microgels resulted in higher M1 polarization or M2 polarization in macrophages, respectively. [79] The inflammatory response of macrophages has also been shown to decrease when the GHS pore size is within the same range of cell size.…”
Section: Resultsmentioning
confidence: 99%
“…[80] GHS with a similar pore size to our GHS-M (average microgel diameter ≈ 70-80 μm) had a significantly higher infiltrated cell area after 21 days of subcutaneous implantation compared with GHS made up of smaller (≈40 μm) or larger (≈130 μm) microgels. [81] Furthermore, the cytotoxicity of scaffolds was assessed clinically via weight, and there was no associated weight loss in any animal cohort. Histology was used to demonstrate end organ normalcy, as shown in Figure 5C.…”
Section: Resultsmentioning
confidence: 99%
“…The fabrication of the PEG μgels used in this work has been described previously by Liu, et al [32] The precursor solution for these μgels included 8-arm PEG Vinylsulfone (PEG-VS), K-peptide (Ac-FKGGERCG-NH2, GenScript), Q-peptide (Ac-NQEQVSPLGGERCG-NH2, GenScript), and RGD (Ac-RGDSPGERCG-NH2, GenScript) in 0.3 m triethylamine (Sigma) buffer. The crosslinker solution was prepared by dissolving the MMP-cleavable peptide (Ac-GCRDGPQGIWGQDRCG-NH2, GenScript) in distilled water at 12 mm and 10 μm Alexa-Fluor 647-maleimide (Invitrogen).…”
Section: Experimental Methodsmentioning
confidence: 99%